Psychological Impact of Paying Zakat Obligations Through Zakat Management Institutions - Rahman, Deni; Rozelan, Ahmad; Silvianetri, Silvianetri (Darussalam: Journal of Psychology and Educational, 2023)
Zakat has a significant Psychic role in society. Therefore, Allah mentions in the Qur'an the commands of zakat and prayer. This shows that the role of psychic zakat is very strong. This research will try to explore and analyze the psychological impact of paying zakat obligations through Zakat Institutions. The method used in this paper is a qualitative method using analytical content. it was found that by paying zakat obligations through the Zakat Management Institution, this would provide peace of mind for the person who paid it, especially when a person performs zakat through the amil zakat body, then he will be prayed for by amil zakat and mustahik . So that has a positive psychological impact.